An Analysis and Design of Simulation Modelling for Airplane Passenger Boarding Strategy during Normal and New Normal Periods - AriantoAjie Nugroho, Muhammad Asrol, Fergyanto E. Gunawan, Abdul Halim, Danny Prastitasari, Rizky Tricahya Kurniawan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Boarding process is the main activity that became the key efficiency in each turnaround process on the airport. The successful in achieving time efficiency will give some benefit to all parties, including airlines, airport management and passengers, especially related to business sustainability, operational and customer satisfaction reasons. The objective of the research is to design an effective model for passenger boarding strategy that focus on airplane with a 180-seat configuration, in scenarios for both normal and new normal periods using agent-based simulation in NetLogo 6.1.1. The simulation output was processed using descriptive and sensitivity analysis and also Chi Square test of independence methods. The simulation results show that Wave strategy which is implemented through the seat-assignment and group-assignment has successfully demonstrated its effectiveness and gives an alternative to be applied by the airlines, for both in normal and new normal periods. By comparing the average boarding time with scenarios in the normal period (load factor 100%) and the new normal period (load factor 66.7%), it is found that the average boarding time by applying 1.0 meter of social distancing is about 78.21%, while for 1.5 meters about 116.06% and for 2.0 meters about 138.29%. Furthermore, by using the Chi Square test of independence analysis, it can be seen that the application of social distancing is highly correlated to the effectiveness boarding strategy.